Republic of Poland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This Selected Issues paper on the Republic of Poland constructs a financial conditions index for Poland to explore the link between financial conditions and real economic activity. Measures to contain the fiscal deficit in the aftermath of the global financial crisis led to a reduction in the headline deficit from 7.9 percent of GDP in 2010 to 3.9 percent in 2012. The authorities plan to implement a permanent fiscal rule. This would complement existing public debt limits, which have proven useful but insufficient in the past. Regarding mechanism design, the authorities have expressed their preference for a simple expenditure rule, on grounds of transparency, predictability, and ease of implementation across budgetary units.